2018
DOI: 10.1177/0011128718779569
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of the Physical Environment on Crime Rates: Capturing Housing Age and Housing Type at Varying Spatial Scales

Abstract: This study introduces filtering theory from housing economics to criminology and measures the age of housing as a proxy for deterioration and physical disorder. Using data for Los Angeles County in 2009 to 2011, negative binomial regression models are estimated and find that street segments with older housing have higher levels of all six crime types tested. Street segments with more housing age diversity have higher levels of all crime types, whereas housing age diversity in the surrounding ½-mile area is ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 59 publications
1
20
0
Order By: Relevance
“…Studies have shown that this process plays out slowly over a long period of time (Hoyt 1933;Rosenthal 2008), but nonetheless older housing units tend to experience turnover in which residents are replaced by those of modestly lower income (Rosenthal 2014). As further evidence of this deterioration, a recent study showed that street segments with older housing had higher levels of crime, which is consistent with this deterioration leading to disorder, which is posited to increase crime (Hipp, Kim, and Kane 2019). The implication is that transitions occurring when households move out of an older housing unit will have greater potential for inducing social distance, and therefore are important to study for understanding neighborhood change.…”
Section: What Are the Determinants Of Social Distance During Residentmentioning
confidence: 79%
“…Studies have shown that this process plays out slowly over a long period of time (Hoyt 1933;Rosenthal 2008), but nonetheless older housing units tend to experience turnover in which residents are replaced by those of modestly lower income (Rosenthal 2014). As further evidence of this deterioration, a recent study showed that street segments with older housing had higher levels of crime, which is consistent with this deterioration leading to disorder, which is posited to increase crime (Hipp, Kim, and Kane 2019). The implication is that transitions occurring when households move out of an older housing unit will have greater potential for inducing social distance, and therefore are important to study for understanding neighborhood change.…”
Section: What Are the Determinants Of Social Distance During Residentmentioning
confidence: 79%
“…On the other hand, BWT links serious crimes to the social and physical disorders, positing that the prevalence of disorder creates fear in the minds of citizens who are convinced that the area is unsafe [16]-which might play an important role in their attitude and behaviors [26]. More recently, many other experimental studies have concluded that in fact there is a significant association between built environment and crimes [1,2,9,13], specifically that poor physically designed urban environment is associated with an increase in crime rates.…”
Section: The Association Between the Built Environment And Crimesmentioning
confidence: 99%
“…The effect of the built environment on crime intensity is consequential and has received growing attention in the literature in crime place studies [1,2]. Crimes depend on demographic and socioeconomic factors, but they also depend on the built environment, which acts as an external force affecting an individual's behavior and attitude [3][4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations